Livestock disease control and the changing landscapes of south-west Ethiopia - Reid, Robin S.; Thornton, Philip K.; Kruska, Russell L. (CAB International, 2001)
This paper examines how controlling livestock trypanosomiasis, transmitted by tsetse-fly (Glossina spp.), affects the rate and location of agricultural expansion in Ghibe Valley, Ethiopia. Control of the disease will reduce animal mortality, increase productivity per animal and cause livestock populations to increase. In turn, this will allow more land to be ploughed and used more intensively for crop production, human nutrition will improve, and migrants will be attracted to new areas. More people and livestock will require greater quantities of fuelwood, wild foods, forage and water.